Oracle JRockit: The Definitive Guide - Hirt, Marcus (Packt Publishing, 2011)
Filled with careful step-by-step instructions and plenty of screenshots, this tutorial shows you JRockit and how to get the most from it. All key concepts in the JRockit JVM, such as code generation, memory management and other internals are introduced. Performance aspects of Java are discussed in detail. A complete guide to use the tools in the JRockit Mission Control suite is also included, and much more. This book is for intermediate to advanced Java Developers, who want to monitor, diagnose, profile and enhance the performance of their Java applications. It is also for people who want to understand more about the internal workings of a modern Java Virtual Machine or adaptive runtime. Parts of the book are suitable as course material for education about runtimes.